The influence of different efficacy constructs on energy conservation intentions and climate change policy support. (June 2021) - Choi, Soobin; Hart, P. Sol
Abstract: This study examines how different efficacy constructs – self efficacy, personal outcome expectancy, collective efficacy, and collective outcome expectancy – independently influence willingness to engage in personal energy conservation behavior and support for policies to address climate change. Data from a representative, cross-sectional survey of 23 countries, European Social Survey Round 8, was analyzed to test the relationship. Overall, the results demonstrated that self efficacy, personal outcome expectancy, and collective outcome expectancy were all positively associated with both behavioral intention and policy support. Results regarding collective efficacy were unstable. The results demonstrate the importance of clearly distinguishing different constructs of efficacy beliefs from each other and suggest how climate change communication efforts may benefit from focusing on particular efficacy factors. Highlights: Distinguishes how four types of efficacy are associated with behavioral intention and policy support. Collective efficacy does not have a robust relationship with behavioral intention or policy support. Self efficacy has a positive association with behavioral intention and policy support. Personal outcome expectancy has a positive association with behavioral intention and policy support. Collective outcome expectancy has a positive association with behavioral intention and policy support.